2017
DOI: 10.1080/14712598.2017.1299705
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of rindopepimut in the treatment of glioblastoma

Abstract: Introduction Rindopepimut (CDX-110) is a peptide vaccine that targets epidermal growth factor receptor variant III (EGFRvIII), a tumor-specific epitope expressed in the most common and lethal primary malignant neoplasm of the brain – glioblastoma (GBM). Areas covered The EGFRvIII mutation introduces an 801 base pair in-frame deletion of the extracellular domain of the transmembrane tyrosine kinase, resulting in constitutive kinase activity, amplification of cell growth, and inhibition of apoptosis. Rindopepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…More recently, it has been shown that multiple subtypes coexist in different regions 20 and different cells 12 within the same tumour. This interpatient and intratumoural heterogeneity poses a daunting challenge for research programs aimed at developing targeted therapeutic approaches 21 and may explain the failures of such approaches in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that multiple subtypes coexist in different regions 20 and different cells 12 within the same tumour. This interpatient and intratumoural heterogeneity poses a daunting challenge for research programs aimed at developing targeted therapeutic approaches 21 and may explain the failures of such approaches in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…blood-brain barrier (12). Bev is a humanized monoclonal antibody directed against VEGF that effects dramatic radiographic responses, improved quality of life, decreased dependence on oral steroids, and improved PFS (12).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Second line chemotherapy is generally in the form of an alkylating agent such as lomustine, or an anti-angiogenic agent such as bevacizumab (Bev) that is FDA approved for this purpose (8)(9)(10)(11)(12). Vascular endothelial growth factor-A (VEGF-A) is a regulator of angiogenesis and the prime driver of endothelial proliferation, a hallmark of GBM.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Such vaccination resulted in prolonged progressionfree and overall survival (OS) with no safety concerns. However, a phase III CT (ACT IV (NCT01480479)) with rindopepimut was discontinued since the study failed to meet its primary OS endpoint [7,17,18]. Another example is a live attenuated Listeria-based vaccine (ADU-623) expressing both EGFRvIII and NY-ESO-1 antigens, which is currently being tested in patients with recurrent GBM through a phase I CT (NCT01967758) [11,18].…”
Section: Peptide and Multipeptide Vaccinesmentioning
confidence: 99%